Changes

,  10:54, 26 August 2013
Line 39: Line 39:
! scope="col" width="225pt" | Notation

! scope="col" width="225pt" | Notation

|-

|-
| Single Variant  || $T=\sum_{i=1}^n {U_i}\bigg/\sqrt{\sum_{i=1}^n{V_i}}$ || $T\sim\mathbf{N}(0,1)$ || $x_i$
+
| Single Variant  || $x_i$ || $T=\sum_{i=1}^n {U_i}\bigg/\sqrt{\sum_{i=1}^n{V_i}}$ || $T\sim\mathbf{N}(0,1)$

|-

|-
| un-weighted Burden      || $T_b=\sum_{i=1}^n{\mathbf{U_i}}\Big/\sqrt{\sum_{i=1}^n{\mathbf{V_i}}}$ || $T_b\sim\mathbf{N}(0,1)$ ||
+
| un-weighted Burden      || $T_b=\sum_{i=1}^n{\mathbf{U_i}}\Big/\sqrt{\sum_{i=1}^n{\mathbf{V_i}}}$ || $T_b\sim\mathbf{N}(0,1)$

|-

|-

| Weighted Burden || $T_{wb}=\mathbf{w^T}\sum_{i=1}^n{\mathbf{U_i}}\bigg/\sqrt{\mathbf{w^T}\left(\sum_{i=1}^n{\mathbf{V_i}}\right)\mathbf{w}}$  || $T_{wb}\sim\mathbf{N}(0,1)$

| Weighted Burden || $T_{wb}=\mathbf{w^T}\sum_{i=1}^n{\mathbf{U_i}}\bigg/\sqrt{\mathbf{w^T}\left(\sum_{i=1}^n{\mathbf{V_i}}\right)\mathbf{w}}$  || $T_{wb}\sim\mathbf{N}(0,1)$
2,004

edits